ACHIEVEMENTS OF THE SCIENTIFIC SCHOOL OF SCIENTIFIC DEVELOPMENT TO THE STUDENT YOUTH OF PROFESSOR G.P. SHEVCHENKO (Pedagogy of Higher and Secondary Education, 2009)
In the article light up basic directions activity of scientific school of spiritual development of student's young people G.P. Shevchenko in the making of the system of professional preparation of pedagogical personnels.
Keywords: professional training; the idea of ​​interaction of the arts; integrated approach